Establishment and Evaluation of a Novel Method Based on Loop-Mediated Isothermal Amplification for the Rapid Diagnosis of Thalassemia Genes [Corrigendum] - Wang W; Lin M; Li H; Huang J; Chen J; Fang X; Huang D; Xi X; Zhao Q; Song F; Huang S; Zhong T (Dove Medical Press, 2021)
Wang W, Lin M, Li H, et al. Risk Manag Healthc Policy.  2020;13:303– 311 On page 309, Sensitivity and Specificity of LAMP Assays in Clinical Assay heading, last sentence “These results showed that the sensitivity and specificity were  99.2% (252/254) and 29.5% (43/146), respectively” should be “These results showed that the sensitivity and specificity were 99.2% (252/254) and 70.5% (103/146), respectively”. The authors apologize for this error and advise it does not affect the conclusions of the paper.  Read the original article